MO511: Epidemiology of Idiopathic Nephrotic Syndrome in Children Before and During Covid-19 Pandemic in Paris Area. (3rd May 2022) - Thenot, Victoire; Parmentier, Cyrielle; Boyer, Olivia; Mahdi, Fouad; Nathanson, Sylvie; Zenkhri, Ferielle; Blanc, Philippe; Mendli, Nasser; Galerne, Aurelien; Mandelcwajg, Alexis; Hogan, Julien; Dossier, Claire
Abstract: BACKGROUND AND AIMS: The aetiology of idiopathic nephrotic syndrome (INS) remains partially unknown. Viral infections have been reported to be associated with INS onset and relapse. The COVID-19 pandemic led to several national lockdowns aimed at limiting virus transmission. In France, schools were closed during the first lockdown (15 March–11 May 2020). Circulation of other respiratory viruses was lower due to restrictive lockdown measures. We hypothesized that these lockdown measures would be associated with a decrease in the incidence of idiopathic nephrotic syndrome in children. The aim of this study was to describe the incidence of INS over the last 4 years and during the lockdown measures and to compare this incidence with the 2007–10 period (NEPHROVIR-1 cohort). METHOD: A written questionnaire was sent to corresponding the paediatricians of all 37 hospitals in the Paris area. Children aged 1–15 years with INS onset between January 2017 and December 2020 and living in the Paris area were included. Clinical data were collected from medical charts. To estimate incidence, population-based denominators were obtained from the National Institute for Statistics and Economic Studies (INSEE). For analyses, we separated the study period into two periods: during lockdown measures (2 months) and the rest of the time (46 months). RESULTS: A total of 95% of centres responded to the questionnaire. On the whole, 248 cases of INS were reported, 94% of whom were steroid sensitive. The median age at diagnosis was 5.6 years. Male/female ratio was 2.1: 1. Annual incidences of INS were 2.66, 2.49, 2.91 and 2.40/100 000 children under age 15 years in 2017, 2018, 2019 and 2020, respectively, with no significant difference between years. There was also no difference between annual incidence of the 2017–20 period and the NEPHROVIR-1 cohort period (2007–10) (P = .6). The incidence of INS during the lockdown measures was 0.51 versus 2.71 for the rest of the study period (P = .03). During week 15 (6–12 April 2020), with the highest number of hospital admissions for COVID-19, no case were reported. CONCLUSION: Over the last decade, the incidence of childhood INS was stable in the Paris area. In 2020, no peak of incidence occurred concomitantly with the COVID pandemic. In addition, during lockdown measures, the incidence of INS was significantly lower. Interestingly, incidence of other respiratory viral infections was reported decreased during lockdown measures. Together, these results argue again for a link between INS onset and viral infections, while COVID-19 does not appear to be a significative trigger for nephrotic syndrome onset in children.